ANALISIS PENGARUH RELIGIUSITAS, ETIKA BISNIS ISLAM TERHADAP MINAT BELI ONLINE MAHASIWA (STUDI KASUS PADA STIE AMM MATARAM) - ulfiyani asdiyansyuri (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
This study aims to see the influence of religiosity and Islamic business ethics on students' online buying interest (Case Study on Students of STIE AMM Mataram). The sample in this study were students of STIE AMM Mataram who were still active. The data were obtained using documentation, interviews and distributing questionnaires to 92 students. The data analysis technique used by the researchers was validity, reliable, classical assumption test and multiple linear regression. The results of data processing with multiple linear regression analysis partially show that the variable responsibility for online buying interest (Y) has a t count greater than t table, namely 4.403> 1.992 with a significant value of 0.008, the variable relationship between honesty (X2) and online buying interest (Y) has t count greater than t table, namely 3.014> 1.992 with a significant value of 0.014. And the relationship variable Religiosity (X3) to online buying interest (Y) has a value greater than the label, namely 3.033> 1.992 with a significant value of 0.032. Partially it has a significant influence on the online buying interest variable. And simultaneously the results of data analysis show the fcount is greater than ftable 21.184> 3.10) and a significant value of 0.000, meaning that the variables of religiosity and pocket money simultaneously have a significant effect on buying interest in foreign students of STIE AMM Mataram.